Short-interval intravenous indocyanine green administration in pediatric laparoscopic cholecystectomy: a prospective evaluation of visualization and safety - Dotlacil, Vojtech; Pajerova, Eliska; Sovadinova, Dagmar; Kucerova, Barbora; Vyhnanek, Martin; Rygl, Michal (Pediatric surgery international, 2025)
PURPOSE: Indocyanine green (ICG) fluorescence imaging enhances biliary visualization during pediatric laparoscopic cholecystectomy (LC), helping to identify anatomical variants and prevent bile duct injury. Standard pediatric recommendations suggest ICG administration 16-24 h preoperatively; however, this may be impractical. This study aims to evaluate the safety and effectiveness of short-interval ICG administration. METHODS: A prospective single-center study (October 2024-June 2025) included pediatric LC patients receiving intravenous Verdye® preoperatively. Visualization of extrahepatic biliary anatomy was assessed intraoperatively using a 5-point Likert scale, HELPFUL (usefulness), and DISTURBED (liver background interference) scores. Data included indication, ICG timing, operative time, and complications according to the Clavien-Dindo classification (C-D). RESULTS: Eleven patients (64% female), median age 14 years (IQR 12,7-15,7) and median weight 65,5 kg (IQR 46,5-80), were included. Five had BMI > 25 kg/m2; five (46%) underwent preoperative ERCP. ICG (median dose 0.34 mg/kg) was administered a median of 225 min before surgery. Median operative time was 65 min (IQR 58-68). Median Likert score was 5; HELPFUL 3; DISTURBED 1. No ICG-related or C-D complications occurred. CONCLUSION: Short-interval ICG administration was safe, feasible, and effective in enhancing biliary visualization during pediatric LC. This approach was well-tolerated and provided high-quality imaging without complications.
Keywords: ženské pohlaví; mladiství; lidé; prospektivní studie; pooperační komplikace; Operative Time; indokyanová zeleň; Optical Imaging; Indocyanine Green; optické zobrazování; studie proveditelnosti; Length of Stay; Child; délka pobytu; Surgery, Computer-Assisted; délka operace; injekce intravenózní; Time Factors; Humans; barvicí látky; Injections, Intravenous; Coloring Agents; Prospective Studies; chirurgie s pomocí počítače; mužské pohlaví; žlučové ústrojí; předoperační péče; Male; Biliary Tract; cholecystektomie laparoskopická; časové faktory; Adolescent; Postoperative Complications; Preoperative Care; Cholecystectomy, Laparoscopic; Female; dítě; Feasibility Studies